THINNING STENTIFORD ALGORITHM FOR KINTAMANI INSCRIPTION IMAGE SEGMENTATION - Christina Purnama Yanti; I Gede Andika (Jurnal Techno Nusa Mandiri, 2020)
In the copper, inscription contained writing strokes that have high historical value. Age and environmental factors cause damage to the inscription surface and also reduce the appearance of images and letters. One way to preserve it is to carry out the process of converting it into digital format. The use of the morphological operation method is very suitable to be used to improve the shape of the letters in the copper inscription. The morphological operations performed in this study were the Thinning Stentiford algorithm. Based on research that has been done, it was concluded that the Thinning Stentiford algorithm has succeeded in segmenting the letters that exist in the Kintamani copper inscription. However, there are some letters are not well segmented. This is due to the inscription background color and carved letter colors that don't have significant differences. Testing the time it was concluded that the greater the size of the image and the more letters will be segmented, the longer the processing computing.